2020
DOI: 10.1136/jmedgenet-2019-106685
|View full text |Cite
|
Sign up to set email alerts
|

Variable expression of subclinical phenotypes instead of reduced penetrance in families with mild triphalangeal thumb phenotypes

Abstract: BackgroundThe of zone of polarizing activity regulatory sequence (ZRS) is a regulatory element residing in intron 5 of LMBR1 and regulates Sonic Hedgehog expression in the limb bud. Variants in the ZRS are generally fully penetrant and can cause triphalangeal thumb (TPT) and polydactyly in affected families.ObjectiveIn this report, we describe two families with mild phenotypical presentation.MethodsWe performed a field study for clinical evaluation and sequenced the ZRS for variantsusing Sanger sequencing.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…At least 20 different SNVs have been reported within the ZRS region in patients with triphalangeal thumb and related diseases: C105 A165 (Potuijt et al, 2020), C287 (VanderMeer et al, 2012), T295 (Furniss et al, 2008), G297 (Albuisson et al, 2011), A305 (Lettice et al, 2003), T323 (Lettice et al, 2003), T334 (Albuisson et al, 2011), C396 (Semerci et al, 2009) and present report, C402 (VanderMeer et al, 2014), G404, A406 (Norbnop et al, 2014; Zhao et al, 2016), A417 (Vanlerberghe et al, 2015) (in mosaic), T428 (Wu et al, 2016), C446 (Xu et al, 2020), T463 (Farooq et al, 2010), T603 (Laurell et al, 2012), a 13 bp insertion (Laurell et al, 2012), C619 (Al‐Qattan et al, 2012), C621 (Gurnett et al, 2007), A739 (Gurnett et al, 2007) (Figure 6). Recently, some other pathogenic changes at the so‐called pre‐ZRS region (pZRS), a region approximately 800 bp upstream from the ZRS, have been related to an indistinguishable similar phenotype (Potuijt et al, 2018; Xiang et al, 2017) to those having a pathogenic variant within the ZRS region (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…At least 20 different SNVs have been reported within the ZRS region in patients with triphalangeal thumb and related diseases: C105 A165 (Potuijt et al, 2020), C287 (VanderMeer et al, 2012), T295 (Furniss et al, 2008), G297 (Albuisson et al, 2011), A305 (Lettice et al, 2003), T323 (Lettice et al, 2003), T334 (Albuisson et al, 2011), C396 (Semerci et al, 2009) and present report, C402 (VanderMeer et al, 2014), G404, A406 (Norbnop et al, 2014; Zhao et al, 2016), A417 (Vanlerberghe et al, 2015) (in mosaic), T428 (Wu et al, 2016), C446 (Xu et al, 2020), T463 (Farooq et al, 2010), T603 (Laurell et al, 2012), a 13 bp insertion (Laurell et al, 2012), C619 (Al‐Qattan et al, 2012), C621 (Gurnett et al, 2007), A739 (Gurnett et al, 2007) (Figure 6). Recently, some other pathogenic changes at the so‐called pre‐ZRS region (pZRS), a region approximately 800 bp upstream from the ZRS, have been related to an indistinguishable similar phenotype (Potuijt et al, 2018; Xiang et al, 2017) to those having a pathogenic variant within the ZRS region (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the proband harbored the compound heterozygote of ZRS (ZRS474C > G and ZRS619C > T). Given that Jacob et al ( 23 ) reported ZRS variant carriers with minor anomalies and underlined the importance of accurate clinical examination in mild triphalangeal thumb families, we carefully checked the phenotypes of her family members with one ZRS variant and did not find any limb defects (cannot completely exclude the possibility of an extremely subtle anomaly) ( 23 ). We reasoned that PPD in this family was attributed to combinedly acting by these two variants.…”
Section: Discussionmentioning
confidence: 99%
“…These mild anomalies might not cause evident aesthetic or functional problems, so the report will indicate that the individual is as unaffected. Consequently, the width, number of flexion folds, strength, and digital opposition of the thumb and whether the lunula of the thumb is duplicated should be evaluated when investigating the patient’s history[ 19 ].…”
Section: Discussionmentioning
confidence: 99%